Using ”Snakes and Ladders’’ Language Game Through Buzz Group to Improve Speaking Ability of the First Grade Students of SMAN 2 Pinrang, Indonesia - Kusuma Wardani, Andi Tri Putri; Nur, Rafi'ah (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2018)
The major problems of this research were how to enhance the students’ speaking ability. Then how to make the students interest to speak in English so this research conducted to find out whether Using ”Snakes and Ladders’’ language game through Buzz Group to Improve Speaking Ability of the First Grade students of SMAN 2 Pinrang. A Mix method was carried out by researcher in this research. The population was the first grade students of SMA Negeri 2 Pinrang. X.exact.1 and X.exact.5 were taken as sample which consists of 31 students for each class X.exact.1 was chosen as the experimental group, while X.exact.5 was chosen as control group. The instruments that used in collecting the data were interview test and questionnaire. The procedure in collecting data were divided into 3 stages namely pre-test, treatment, and post-test. The data obtained through the test were analyzed quantitatively and qualitatively. The result of the research shows the students’ speaking ability of the experimental was better than the control group. It was proved by the data of the students’ mean score on experimental class was higher tha the control group (78.67 ˃ 60.22). Futhermore, Using ”Snakes and Ladders’’ language game through Buzz Group to Improve Speaking Ability of the First Grade students of SMAN 2 Pinrang Besides, the research finding also shows the students interest toward the implementing of this simulation. It was proved by the data from questionnaire that the students’ interest was which categorized as strongly agree.